Модернізація стратегічних галузей національної економіки в умовах децентралізації - Кушніренко, О.М. (Вісник економічної науки України, 2023)
Ключова роль модернізації промисловості в забезпеченні стійкості національної економіки актуалізує проблему науково обґрунтованого вибору інструментів, які ефективно працюють в умовах децентралізації. У даному дослідженні до стратегічних галузей національної економіки віднесено ті, які забезпечені власною ресурсною, виробничою, науково-освітньою базою та мають перспективи інтеграції до глобальних ланцюгів доданої вартості, а саме: чорна металургія; машинобудування; галузі з видобування критичної сировини. У статті узагальнено світові практики кластерного руху та діяльності індустріальних парків, які стали передумовою стійкого промислового розвитку на високотехнологічній основі. Наведено результати опитування учасників індустріальних парків і запропоновано напрями об’єднання спільних зусиль для їх подальшого розвитку. The key role of industrial modernization in ensuring the sustainability of the national economy highlights the problem of a scientifically based choice of tools that working effectively in a decentralized environment.
In this study, strategic sectors of the national economy include those that are provided with their own resource, production, scientific and educational base and have prospects for integration into global value chains, namely: ferrous metallurgy; mechanical engineering; industries for the extraction of critical raw materials. The article summarizes the world practices of cluster movement and activities of industrial parks, which have become a prerequisite for sustainable industrial development on a high-tech basis. The results of the survey of participants of industrial parks are given. The key obstacles hindering the development of industrial parks have been identified and directions of joint efforts have been proposed, namely, involvement in the global trend of sustainable development of the EU and the vector of carbon neutrality within the framework of the European Green Deal; creation of a Development Fund that will provide financial, technical and consulting assistance to participants in industrial parks; creation of a digital platform for potential foreign investors, where investment projects and opportunities in Ukraine will be announced; strengthening cooperation between the participants of industrial parks to attract grant funds for the development of their own ecosystem and the formation of a consolidated position on strategic development with state and regional authorities. Additional effects conducive to the modernization of strategic industries, namely the promotion of innovative development and areas of research and development (DiR); Improving production efficiency through more efficient use of resources; development of innovative infrastructure, support for small and medium-sized businesses.